Pen computers simplify projects. - Thierrin, Raymond (American City & County, 1995)
New digital collection equipment makes the data collection and management process easier on municipal projects. The most exciting new developments are in pen computers, which are handheld devices that use a stylus to enter data. Information can be written directly onto the computer screen, and lettering is changed into text through handwriting recognition. Software converts the information into a computer-readable format and stores it as a data record.